Clinical profile and oral sub mucous fibrosis - Bhatta, Rishi; Pyakurel, M. (Nepalese Journal of ENT Head and Neck Surgery, 2017)
Objectives: Oral submucous fibrosis (OSMF) is an insidious precancerous disease mostly seen in the Southeast Asia. This paper aims to study on clinical profile of patients with OSMFMaterial and Methods: This cross sectional study was done in department of ENT and HNS, Nepalgunj Medical College and Teaching Hospital. In outpatient department patients with OSMF were ask to fill up a questionnaire that included identification of patient, occupation, their symptoms and habit of taking betel quid or paan, gutkha, etc. Oral cavity was examined and lesion along with its extent and severity was noted. Intra lesional steroid and antioxidant and physiotherapy were main stay of treatment.Results: There were total 136 patients (98 male and 38 female) from 15th Dec 2013 to 15th Jan 2015. Age of patient ranged from 16 years to 53 years and average being 25.6years. Most common preparation taken was gutkha 131(96.3%) followed by betel nut, betel quid etc. Only 24(17.6%) were taking these preparations for less than 1 year. Common presenting complaints were difficulty in opening mouth followed by burning sensation and dryness of mouth. Clinically, the extent of fibrous band was found to be more commonly involving soft palate, pillars and buccal mucosa. Isolated involvement of different region of oropharynx or oral cavity was less common. Correlation of grade of trismus and average duration of taking these different preparations was highly significant. (p=0.008)Conclusions: Oral submucous fibrosis is commonly associated with intake of gutkha having dose dependent relationship with trismus. Further studies are required why only a small fraction of those using betel quid develop the disease.